Results of a fast-track HIV and hepatitis C screening protocol in Barcelona, Spain - Chivite, Iván; Guilera, Vanessa; Callau, Pilar; Aguiló, Raquel; de Lazzari, Elisa; Merino, M.J.; Diaz, Laia; Carrodeguas, Alba; González-Sánchez, José Luis; Mallolas, Josep (PLOS ONE, 2025)
Introduction Human immunodeficiency virus (HIV) and hepatitis C virus (HCV) continue to be a significant public health concern. Screening is a critical strategy for HIV and HCV control to reach the World Health Organization’s elimination goals by 2030. This study assessed the outcomes of a healthcare quality improvement project integrating routine opportunistic BBV screening and linkage to care in emergency services for high-risk patients. This project aimed at providing HIV and HCV fast-track screening among patients seeking care in the emergency department of Hospital Clínic de Barcelona (Spain) and re-engage individuals previously diagnosed but not currently in care. Methods This observational study included patients ≥18 years old who presented to the emergency department reporting genitourinary complaints or recent high-risk exposures for HIV, HCV, or other sexually transmitted infections. Using the FOCUS TEST model as a framework, a systematic opportunistic HIV and HCV screening and offered linkage to care (LTC) to patients with positive test results was conducted. Screening was performed using fourth-generation chemiluminescence immunoassays for HIV and HCV antibodies, including p24 antigen detection, with confirmatory HCV RNA testing by PCR. The FOCUS TEST model supports automatic integration of testing into routine workflows and staff training. For each of these blood-borne viruses, the screening volume, testing uptake, seroprevalence, characteristics of patients with new infections, and LTC rates were analyzed. Results Between January 2020 and December 2022, 35,285 blood-borne virus tests were performed. The number of new infections detected was 38 for HIV (0.41% seroprevalence) and 34 for HCV (0.19% HCV RNA prevalence). LTC was achieved for 89% and 100% of patients diagnosed with new HIV and HCV infections, respectively. A separate set of patients with HIV (n = 297) or HCV (n = 25) infections identified prior to this screening program were re-linked to care via this project. Conclusion This healthcare quality improvement project was feasible and successful in achieving its goal of providing systematic opportunistic HIV and HCV screening to patients seeking urgent care. Importantly, the program also enabled LTC of a considerable number of patients previously diagnosed but not retained in care, further strengthening its impact on public health. These outcomes align with global goals for the elimination of HIV and HCV as public health threats by 2030 and demonstrate that similar fast-track screening and linkage strategies could be effectively implemented in other urban emergency settings with appropriate infrastructure and support.